eIF4E Phosphorylation Influences Bdnf mRNA Translation in Mouse Dorsal Root Ganglion Neurons - Moy, Jamie K.; Khoutorsky, Arkady; Asiedu, Marina N.; Dussor, Gregory; Price, Theodore J. (Frontiers in Cellular Neuroscience, 2018)
Plasticity in dorsal root ganglion (DRG) neurons that promotes pain requires activity-dependent mRNA translation. Protein synthesis inhibitors block the ability of many pain-promoting molecules to enhance excitability in DRG neurons and attenuate behavioral signs of pain plasticity. In line with this, we have recently shown that phosphorylation of the 5′ cap-binding protein, eIF4E, plays a pivotal role in plasticity of DRG nociceptors in models of hyperalgesic priming. However, mRNA targets of eIF4E phosphorylation have not been elucidated in the DRG. Brain-derived neurotrophic factor (BDNF) signaling from nociceptors in the DRG to spinal dorsal horn neurons is an important mediator of hyperalgesic priming. Regulatory mechanisms that promote pain plasticity via controlling BDNF expression that is involved in promoting pain plasticity have not been identified. We show that phosphorylation of eIF4E is paramount for Bdnf mRNA translation in the DRG. Bdnf mRNA translation is reduced in mice lacking eIF4E phosphorylation (eIF4ES209A) and pro-nociceptive factors fail to increase BDNF protein levels in the DRGs of these mice despite robust upregulation of Bdnf-201 mRNA levels. Importantly, bypassing the DRG by giving intrathecal injection of BDNF in eIF4ES209A mice creates a strong hyperalgesic priming response that is normally absent or reduced in these mice. We conclude that eIF4E phosphorylation-mediated translational control of BDNF expression is a key mechanism for nociceptor plasticity leading to hyperalgesic priming.